2010
DOI: 10.1089/apc.2009.0224
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric HIV Clinical Care Resources and Management Practices in Asia: A Regional Survey of the TREAT Asia Pediatric Network

Abstract: Characterizing intraregional differences in current pediatric HIV care and treatment in Asia can guide the development of clinical practice guidelines and improve the understanding of local resource availability. The Therapeutics Research, Education, and AIDS Training in Asia (TREAT Asia) Pediatric Program is a collaboration of clinics and referral hospitals studying pediatric HIV outcomes in the region. A Web-based survey to characterize clinical management practices and monitoring resources was developed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Recently, the National Health Security Office, which provides ART to almost all HIVinfected Thai children, reported that 20% of HIV-infected Thai children are receiving second-line PI regimens. The regional Asian network, Treat Asia, which follows over 1000 children, also reported that 20% of children were on second-line ART [19].The children in our study were from eight large paediatric HIV centres in Thailand. Similar to other studies on children from South Africa [6] and Thailand [8,18], extensive NRTI mutations were found.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Recently, the National Health Security Office, which provides ART to almost all HIVinfected Thai children, reported that 20% of HIV-infected Thai children are receiving second-line PI regimens. The regional Asian network, Treat Asia, which follows over 1000 children, also reported that 20% of children were on second-line ART [19].The children in our study were from eight large paediatric HIV centres in Thailand. Similar to other studies on children from South Africa [6] and Thailand [8,18], extensive NRTI mutations were found.…”
mentioning
confidence: 66%
“…Recently, the National Health Security Office, which provides ART to almost all HIVinfected Thai children, reported that 20% of HIV-infected Thai children are receiving second-line PI regimens. The regional Asian network, Treat Asia, which follows over 1000 children, also reported that 20% of children were on second-line ART [19].…”
Section: Discussionmentioning
confidence: 99%
“…MTCT can also be prevented by reducing unwanted pregnancies [3]. Pediatric HIV treatments include variations in formula feeding or exclusive breastfeeding [9]. Ultimately, diagnosis of infants during their early stages of life enables them to benefit most from life-saving drug treatments.…”
Section: Figurementioning
confidence: 99%
“…A crosssectional survey of 17 sites in six Asian countries completed in April 2008 showed that 20% of 3606 children receiving ART had progressed beyond first-line therapy. [64] A more recent survey that analysed data from 10 Asian and 16 southern African sites showed that 10% of 1301 Asian children and 3.3% of 4561 southern African children had initiated second-line therapy. [65] Switching to second-line therapy in RLS has been constrained by unclear criteria for diagnosing treatment failure, and the inaccuracy of clinical and immunological criteria for identifying children with treatment failure.…”
Section: Second-line Recommendationsmentioning
confidence: 99%